ANALYSIS OF PHOSPHORESCENCE EVENTS IN COSINE 100 EXPERIMENT FOR DARK MATTER SEARCH - Prihtiadi, Hafizh (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2025)
The existence of dark matter is supported by strong astrophysical and cosmological evidence, yet its particle nature remains unresolved. In over two decades of direct detection searches, DAMA/LIBRA remains the only experiment to report an annual modulation in NaI(Tl), a result in strong tension with the null findings of other detection technologies. Motivated by this discrepancy, the COSINE experiment is a direct dark matter search using the same NaI(Tl) target material as DAMA/LIBRA operated at the Yangyang Underground Laboratory (Y2L). The COSINE is designed to provide an independent test of the DAMA/LIBRA claim. Here, we analyze the COSINE-100’s findings, which show no evidence for modulation consistent with dark matter interactions and place stringent limits on Weakly Interacting Massive Particles (WIMPs) parameter space. We further discuss the implications of these findings for the DAMA anomaly, the role of complementary NaI(Tl)-based efforts such as ANAIS and SABRE, and the impact on dark matter searches.